Corpos abertos: sobre enfeites e objetos na Vila de Cimbres (T.I. Xukuru do Ororubá) - Lima, Clarissa de Paula Martins (Universidade Federal de São Carlos, 2013)
Talk about their existences through objects and ornaments (enfeites) is something the residents of the Village of Cimbres (Terra Indígena Xukuru do Ororubá) constantly do. This work is, in this sense, an endeavor to pursue them, people, objects and adornments likewise, through the paths they trace, the connections they engender and, at the same time, constitute all of them. As I seek to discuss in this text, something enable objects and ornaments in being active parts in person making, and vice versa: the capacity of everything that is matter to be occupied by existences that go beyond their boundaries, something that constitutes them and is always open to continuous changes. This capacity makes possible to access many portions of Xukuru world through objects and adornments. Thus, looking to the Xukuru through those artifacts, I aim to set forth the multiple connections that they create, and are creating them respectively, and that concerns to relatives and families, person making, politics, cosmology and so on. This text is an exercise to, just as the Xukuru do, look into their world through their objects.
Keywords: Etnologia; Índios Xukuru; Vila de Cimbres (PE); Objetos; Enfeites; Xukuru do Ororubá; Village of Cimbres; Objects; Ornaments; CIENCIAS HUMANAS::ANTROPOLOGIA